International livestock and one health research priorities: Perspectives from Southeast Asia - Hung Nguyen-Viet (International Livestock Research Institute, 2014)
To mark 40 years international livestock research, Hung Nguyen-Viet (ILRI Vietnam) reflects on a recent discussion at a regional workshop one health.